Tanggap Kedaruratan Tersedak Anak Dan Penatalaksanaan Pada Keluarga Di Kelurahan Balocci Baru Kec. Balocci Kab. Pangkep - Salaman Alhidayat, Nurun; Esti Handayani, Dwi; Halimah, Nur; Samsir, Samsir; Alamsyah, Alamsyah; Hasbullah, Hasbullah; Sulasri, Sulasri; Botutihe, Fauziah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Choking is a condition where the upper airway is blocked by food or other objects which causes breathing problems. The method used in this Community Service Activity (PKM) starts from the initial survey, problem formulation, pre test, activity implementation and post test. The results of the activity showed that there was a significant increase in the level of knowledge of parents in providing first aid for choking events in children. The results of the presentation showed that 63% experienced a good increase in knowledge and 37% experienced a moderate increase. It is hoped that this community service activity will help the community, especially parents who have school-age children who are prone to choking, can provide first aid to prevent disability or death